An Experimental Study of RAFT Strategy on Students’ Writing Ability - Syaveny, Niza; Lukmana, Fendi; Wati, Siska Oktawidya; Johari, Indra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This research was experimental research. This research had purpose to find the effect of using RAFT strategy towards students’ writing achievment at grade VIII SMP N 4 Batang Anai. Instruments of this research was writing test. this research used cluster random sampling. Samples of this research were class VIII 2 as experimental class and VIII 3 as control class. Experiment class was taught by RAFT strategy and control class was taught by conventional strategy. Based on the result of research that gotten by post test score. The analysis result showed that the mean score of experimental class was 76.79 with standard deviation was 7.54 and the mean score of control class was 69.43 with standard deviation was 7.39. So, it could be concluded that the RAFT strategy gave significant effect towards students’ writing ability than conventional strategy. It also was supported by the result t-calculated 1.93 > t-table 1.67. So that H1 was accepted and Ho was rejected.